ETIKA DISKURSUS BAGI MASYARAKAT MULTIKULTURAL: Sebuah Analisis dalam Perspektif Pemikiran JÃ¼rgen Habermas - Supartiningsih, Supar (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2007)
Nowadays, multicultural society with its ideology: multiculturalism, has been paid much attention from many people. The concept has been predicted as an effective solution for conflict problems in plural societies. JÃ¼rgen Habermas, in this case, has offered his concept: discourse ethics, which gives interest to an ability for discourse. The goal of this research is to find the relevancy of the discourse ethics for multicultural society. To what extent the challenge of multicultural society could be answered by the discourse ethics. This writing shows that the discourse ethics has offered an ethical dimension in which be constructed socially for values preference. It is decided by a rational discourse. The rational discourse is a responsibility discourse which pays attentions to validity claims. The reconstruction of new values in the discourse will drive to formation of a new world which is objective and becomes a life-world where we live together. The model of multicultural society with its plurality needs discourse ability. It is hoped that with the ability people can avoid appearance of conflicts. For this, multicultural educations could be an effort to support growth of multicultural consciousness.